Size-Dependent Catalytic Activity of Oxo-Hydroxo Titanium Sub-Nanoislets Grafted on Organically Modified Mesoporous Silica - Fang, Lin (Langmuir : the ACS journal of surfaces and colloids, 2018)
The reaction between titanium alkoxides, [Ti(OR)4], and surface silanol groups is widely used to generate grafted oxo-hydroxo titanium species, whose size is difficult to control. Partial capping of the surface silanols in the presence of the masking pattern of self-repelling tetramethylammonium ions allows us to isolate surface silanol islets, on which isolated titanium ions and dimeric oxo titanium species can be generated up to 2 Ti/Si mol %. Above this loading, and up to ∼8 Ti/Si mol %, higher oligomers (trimers, hexamers, octamers, and so on) are formed, reaching the size obtained at much lower loadings (<1 Ti/Si mol %) on a nonmodified silica surface. The downsizing effect produced on our organically modified surface is monitored from the blue-shift of the charge-transfer band of the Ti(IV) ions, measured by reflectance UV-visible spectroscopy. It is also mirrored by a higher catalytic activity in cyclohexene epoxidation, revealing that it is not only the isolated Ti species that are active but also the oligomers. Regarding the latter, the smaller they are, the more active they are